PERALIHAN PIUTANG DAN IMPLIKASINYA TERHADAP HAK TANGGUNGAN: STUDI KASUS PUTUSAN NOMOR 202/PDT/2021/PT DKI - Parawansah, Khopipah Indar; Yetniwati; Raffles (Jurnal Yuridis, 2025)
Abstract The objectives of this research are 1) To analyze the effect of transfer of receivables on mortgage rights as debt collateral, especially in the aspect of legal certainty for creditors and debtors. 2) To examine the legal consequences of the transfer of receivables on the validity and implementation of mortgage rights based on Decision Number 202/PDT/2021/PT DKI, as well as the implications for the parties involved. With these objectives, the problems discussed are 1) How is the effect of transfer of receivables in the context of mortgage rights as debt collateral. 2) What are the legal consequences of the transfer of receivables on the validity and implementation of mortgage rights in Decision Number 202/PDT/2021/PT DKI. With the formulation of these problems, this research uses normative juridical research with a statutory approach (statue approach), conceptual approach (conceptual) and case approach (case approach) using agreement theory, legal certainty theory, responsibility theory. The data is reviewed through a literature study of laws and regulations, legal doctrine, and analysis of relevant court decisions.The results show that the transfer of receivables that is not accompanied by notification to the debtor, as stipulated in Article 613 of the Civil Code, does not bind the debtor and has the potential to cause legal disputes.In Decision Number 202/PDT/2021/PT DKI, the transfer of receivables made by PT Bank UOB Indonesia to a third party without prior notification to the debtor was declared legally invalid because it did not fulfill the normative provisions, including the absence of re-binding of the mortgage.This creates legal uncertainty and harms the rights of the debtor.In addition, the process of exercising the mortgage rights by a third party cannot be legally implemented due to the loss of formal legal relationship between the new creditor and the collateral object. The conclusion of this research emphasizes the importance of debtor notification in the cessie process, as well as the need for strict legal procedures in the transfer of receivables secured by mortgage rights so as not to cause violations of the principle of good faith and legal protection for all parties.The suggestions made are that every transfer of receivables should be accompanied by written notification to the debtor and re-recording of mortgage rights in order to ensure legal certainty and justice in banking practice. Keywords : Transfer of Receivables, Mortgage Rights, Cessie, Debtor, Legal Certainty.